Protective Effects of Resveratrol Against Adenomyosis in a Mouse Model. Issue 1 (20th March 2023) - Zhu, Bo; Zhang, Chenhui; Shen, Xiaolu; Chen, Cong; Chen, Xuanyu; Lu, Yiyi; Chen, Yumei; Guo, Min
Adenomyosis is a uterine condition in which endometrial glands and stroma are commonly pathologically observed in the myometrium. In this study, we sought to determine the effect of resveratrol on the progression of adenomyosis. Adenomyosis was induced in mice given tamoxifen neonatally. All mice were subjected to body weight measurement and hotplate testing every four weeks beginning four weeks after birth. All mice with adenomyosis were randomly separated into 3 groups at 16 weeks: untreated, low-dose resveratrol (25 mg/kg), and high-dose resveratrol (50 mg/kg). After 3 weeks of treatment, final hotplate test and body weight measurement were performed, and the uterine horn blood samples were collected. Adenomyosis in mice caused body weight loss and uterine weight gain, reduced hotplate latency, and progression of endometrial fibrosis. The underlying biological process could be coupled with the overexpression of many cells' proliferation and immune-regulation–related genes. Resveratrol treatment could slow the progression of adenomyosis by enhancing hotplate latency, lowering endometrial fibrosis, and restoring cell proliferation- and immune-regulation-associated gene expression levels in endometrium and plasma. However, resveratrol treatment also reduced the body weight and uterine weight. In conclusion, Resveratrol might be a potential compound for treating patients with adenomyosis.